Assessment of the heat and moisture transfer in a multilayer protective fabric system under various ambient conditions. Issue 3 (February 2015) - He, Jiazhen; Li, Jun; Kim, Eunae
This study was conducted to investigate the effect of multilayer protective clothing on heat and moisture transport under various ambient conditions. By using the Human-Clothing-Environment simulator, a four-layered clothing system was exposed to a high rate of sweat pulse for a duration of 3 hours in seven different ambient conditions: extremely hot and humid (EH, 40℃, 90% relative humidity (RH)), extremely hot and dry (ED, 40℃, 30% RH), hot and humid (HH, 34℃, 75% RH), hot and dry (HD, 34℃, 30% RH), warm and dry (WD, 27℃, 30% RH), slightly cold (SC, –3℃, 20% RH) and cold (CO, –10℃, 20% RH). The temperature and RH in the microclimate were measured and the distribution of within layers was analyzed. Several dynamic stage changes of the microclimate were observed throughout the test. Variations in ambient condition have an effect on the microclimate and the distribution of moisture accumulated within layers. Heat and moisture transport through the clothing system would be influenced by the condensation within layers. In cold conditions, 80% of the moisture accumulated in the clothing system was located in the thermal liner and moisture barrier, whereas in other conditions, most of it was accumulated in the thermal liner.